ANALISIS KETERAMPILAN ARGUMENTASI DAN BERPIKIR KRITIS SISWA PADA MATERI EKOSISTEM KELAS VIII SMP - Wulandari, Aji Intan Nispu; Nasution, Ruqoyyah (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This study aims to analyze how students' argumentation and critical thinking skills are and to find out whether there is a relationship between students' argumentation and critical thinking skills in the class VIII ecosystem material of SMP Negeri 37 Samarinda for the 2023/2024 school year. This type of research is qualitative. The population in this study is all grade VIII students of SMP Negeri 11 Samarinda for the 2023/2024 school year consisting of 4 classes of 277 students and a selected sample of 45 randomly selected students. The data in this study was obtained using question instruments to measure argumentation skills and questionnaires to measure critical thinking skills. Furthermore, the data of this study were analyzed using descriptive statistics and non-parametric statistics. The results showed that students' argumentation skills were still at levels 1-3 with an average percentage of 47.56% which was included in the sufficient category, while students' critical thinking skills had an average of 71.5% which was included in the high category. The significance value of the correlation between argumentation skills and critical thinking is 0.788, which means there is no relationship between the two variables.